Инженерные расчеты. Книга-билингва: учебное пособие - Очков В. Ф. Валерий Федорович; Орлов К. А. Константин Александрович; Тихонов А. И. Антон Иванович; Гуличева Е. Г. Елена Геннадьевна; Чудова Ю. В. Юлия Владимировна (Высшее образование)
Текст парал. на англ. и рус. яз.